Evoluç\~ao recente do comércio exterior brasileiro com os países do Mercosul - Sérvulo Vicente Moreira; Ethianne Érica Lucena Milhomem (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper presents the commerce evolution performance among Mercosul countries, as well as the external Brazilian commerce evolution with Mercosul member's countries. As presented by the tables, the increasing commerce creation into the regional block demonstrates its strength and the need of new institutions in order to facilitate the regional block by transforming it in a common market. The main conclusion is related in how the regional block is essential for the Brazilian exports, as it currently absorbs around 20% of Brazilian annual exports.
Keywords: F15; 330; Internationale Wirtschaftsbeziehungen; Mercosur-Staaten